2016
DOI: 10.1097/tp.0000000000001191
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Reactive Regulatory T Cell Frequency Increases During Acute Cellular Rejection of Lung Allografts

Abstract: Background Acute cellular rejection is a major cause of morbidity following lung transplantation. Because regulatory T cells (Treg) limit rejection of solid organs, we hypothesized that donor-reactive Treg increase after transplantation with development of partial tolerance and decrease relative to conventional CD4+ (Tconv) and CD8+ T cells during acute cellular rejection. Methods To test these hypotheses, we prospectively collected 177 peripheral blood mononuclear cell (PBMC) specimens from 39 lung transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…17 Maintenance of immunosuppressant therapy included tacrolimus, prednisone, and mycophenolate mofetil. 17 Maintenance of immunosuppressant therapy included tacrolimus, prednisone, and mycophenolate mofetil.…”
Section: Study Population and Standard Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Maintenance of immunosuppressant therapy included tacrolimus, prednisone, and mycophenolate mofetil. 17 Maintenance of immunosuppressant therapy included tacrolimus, prednisone, and mycophenolate mofetil.…”
Section: Study Population and Standard Therapiesmentioning
confidence: 99%
“…for approximately 20% of the lung transplant recipients based on surgeons' preferences. 17 Maintenance of immunosuppressant therapy included tacrolimus, prednisone, and mycophenolate mofetil.…”
mentioning
confidence: 99%
“…A recent study finds that donor-reactive Treg is minimally impacted in lung transplant patients after basiliximab induction 53 . Treg normally express low levels of the IL-7 receptor α chain CD127 54,55 .…”
Section: Impact Of Approved Immunosuppressive Drugs On Tregmentioning
confidence: 99%
“…One might speculate that IFNy+ Treg are induced when they are needed. A recent publication reports that, contrary to expectation, overall proportions of donor-reactive Treg are similar before and after lung transplantation and increase during acute A2 cellular rejection of lung allografts, suggesting a mechanism how A2 rejection might be self-limiting [25]. The authors noted that the observed increases over baseline donor-reactive Treg were insufficient to prevent acute lung allograft rejection [25].…”
Section: Discussionmentioning
confidence: 98%